2011
DOI: 10.2106/jbjs.j.01255
|View full text |Cite
|
Sign up to set email alerts
|

Safety Syringes and Anti-Needlestick Devices in Orthopaedic Surgery

Abstract: The most effective and reliable safety devices for orthopaedic syringe procedures are shielded safety needles, mechanical syringes, manual retractable syringes, and shielded syringes, but not automatic retractable syringes. Even when adopting safety-engineered devices for an orthopaedic clinic, conventional syringes larger than 20 mL and conventional needles longer than 1.5 in (3.8 cm) are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
(87 reference statements)
0
8
0
2
Order By: Relevance
“…The observation identified no accidental needle sticks (0 needle sticks per 1300 devices). The author concluded that the shielded safety needles, mechanical syringes, manual retractable syringes, and shielded syringes, are effective, reliable and safe for orthopaedic syringe procedures 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation identified no accidental needle sticks (0 needle sticks per 1300 devices). The author concluded that the shielded safety needles, mechanical syringes, manual retractable syringes, and shielded syringes, are effective, reliable and safe for orthopaedic syringe procedures 8 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that an orthopedics surgeon's risk of sharp injury is as high as 80%-90% in a 10-year period. 8 The mean exposure rate among the orthopaedic surgeons is 1.4 per year with only 33 % reporting the incident. The reason for not reporting was identified as a perceived low risk of the patient carrying the blood borne infections and possible stigmatization and loss of employment [9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the included studies, five were conducted in the United States (23)(24)(25)(26)(27) , two in Brazil (28)(29) , one in France (30) , one in Italy (31) , one in Scotland (32) and one in Lebanon (33) . Regarding authorship, six studies were carried out by physicians (23)(24)27,(29)(30)34) , four by professionals with a degree in science (25,28,(31)(32) and one per nurse (26) . About the type of publication, ten are articles and one is systematic review (33) .…”
Section: Resultsmentioning
confidence: 99%
“…Encontraram-se estudos que relataram o modo de operação de tais dispositivos de segurança, sendo divididos em passivos, em que não há necessidade do usuário ativar o recurso de segurança, e ativos, que exigem que o usuário acione o recurso de segurança. Além disso, podem ser classificados como automático, semiautomático e de ativação manual [14][15][16] .…”
Section: Dispositivo De Segurança Em Instrumentos Perfurocortantesunclassified
“…Safety syringes and anti-needlestick devices in orthopaedic surgery: Testou diversos perfurocortantes com diferentes dispositivos de segurança. Durante os testes, não houve acidentes perfurocortantes, porém constatou-se que alguns modelos eram mais eficazes do que outros, dependendo do procedimento 15 .…”
Section: Safety-engineered Needle Devices: Evaluation Prior To Introdunclassified